The commodification of adult education - Derek Briton; Donovan Plumb (Adult Education Research Conference, 1993)
This paper discusses the consequences of cultural commodification for emancipatory adult education, arguing that while cultural commodification may generate a greater demand for adult education such market-driven programming will be stripped of any emancipatory potential.